Traversable Wormholes Existence in fR,T Gravity Involving Trace-Squared Term with Nonexotic Matter - M. Zubair; Quratulien Muneer; Saira Waheed (Advances in Astronomy)
In Einstein’s relativity theory, the existence of traversable wormholes requires the involvement of exotic matter which violates the null energy condition (NEC). Our aim, in this article, is to construct wormhole solutions with the nonexotic matter. To achieve this, we choose an interesting gravitational framework of fℛ,T theory which contains a quadratic term of energy-momentum tensor Tij trace and a well-known Starobinsky fℛ model in its extended form. We analyze the behavior of energy constraints in the framework of fℛ,T=ℛ+αℛ2+γℛn+λT2 (where α, γ, and λ are some random constants) model for the well-proposed shape function Sr=r0r0/rε (where ε is a constant and r0 is the wormhole throat). A detailed analysis of validity regions is presented for some choices of coupling parameters along with the free parameter of EoS β,m. It is shown that, under this model, the existence of viable wormhole geometry is possible without requiring any exotic matter.